Diaphragm with active coating for battery and preparation method of diaphragm

By applying an active coating containing [Pyr13][TFSI] on the lithium-ion battery separator, the shortcomings of traditional separators in wetting, thermal stability and lithium dendrites inhibition ability are solved, and the performance of the battery is significantly improved and Security.

CN119481570APending Publication Date: 2025-02-18HEFEI HUIQIANG NEW ENERGY MATERIAL TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411737650.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Traditional lithium-ion battery separators have shortcomings in wetting, thermal stability and lithium dendrites suppression capabilities, which affect battery performance and safety.

Method used

Using a separator with an active coating, the coating consists of N-methyl-N-propylpyrrolidine bistrifluoromethanesulfonylimide salt ([Pyr13][TFSI]) and other ceramic materials, coated in polyacyl On imine or other polymer base films, the thermal stability and ion conductivity of the separator are enhanced.

Benefits of technology

It improves the thermal stability and ion conductivity of the diaphragm, reduces the internal resistance of the battery, improves the charge and discharge efficiency and cycle life, and ensures the stability and safety of battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005161869640000081
    Figure BDA0005161869640000081
  • Figure BDA0005161869640000091
    Figure BDA0005161869640000091
Patent Text Reader

Abstract

The invention provides a diaphragm with an active coating for a battery and a preparation method of the diaphragm. The diaphragm is composed of a diaphragm substrate and a composite coating coated on the substrate, the composite coating comprises an outer coating and an inner coating, wherein the outer coating contains N-methyl-N-propyl pyrrolidine bis (trifluoromethanesulfonyl) imide, and the inner coating contains any one or more of polyacrylic acid, a metal organic framework compound, modified boehmite, polyvinylidene fluoride and polymethyl methacrylate. The N-methyl-N-propyl pyrrolidine bis (trifluoromethanesulfonyl) imide salt is coated on the diaphragm, so that the thermal stability and the ionic conductivity of the diaphragm can be enhanced, the internal resistance of the battery is reduced, the charge-discharge efficiency of the battery is improved, the cycle life of the battery is prolonged, and meanwhile, the potential harm to the environment is relatively small. The N-methyl-N-propyl pyrrolidine bis (trifluoromethanesulfonyl) imide salt has good compatibility with the electrolyte of the lithium ion battery and is not easy to generate chemical reaction, so that the performance stability and the safety of the battery are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of preparation of battery coated diaphragms, and in particular to a diaphragm with an active coating for a battery and a preparation method thereof. Background Art

[0002] With the rapid development of portable electronic devices, electric vehicles and grid-scale energy storage, lithium-ion batteries have been widely used due to their high energy density, long cycle life and environmental friendliness. However, the performance and safety of lithium-ion batteries still face some challenges, among which separators play a vital role.

[0003] Traditional polyolefin separators, such as polyethylene (PE) and polypropylene (PP), are widely used in commercial lithium-ion batteries due to their low cost and relatively balanced performance. However, these separators have some inherent disadvantages, such as poor wettability, which makes it difficult for the electrolyte to fully infiltrate, thus affecting the ion transmission efficiency; low thermal stability, easy to shrink, melt or even cause short circuit at high temperature, posing a safety hazard; in addition, they have a weak ability to inhibit the growth of lithium dendrites, which may penetrate the separator, causing internal short circuit of the battery, affecting the performance and safety of the battery.

[0004] In order to improve these problems, researchers have adopted a variety of strategies. For example, designing multi-layer separators, such as PP / PE, PP / PE / PP, etc., and then introducing a thermal shutdown function to melt the low melting point layer at high temperature and close the pores to prevent ion transmission and reduce the risk of thermal runaway. However, this multi-layer structure will increase the thickness of the separator, thereby reducing the energy density of the battery. Intermittent changes in local temperature may lead to a reduction in the ion conduction area and even cause battery failure.

[0005] Another approach is to integrate inorganic materials into polyolefins or coat the surface of the separator with organic / inorganic substances, such as ceramic nanoparticles, to improve the electrolyte wettability and thermal stability of polyolefin-based separators, which is widely used in industrial applications, but has some limitations. For example, separators with less ceramic material content or thinner coatings have limited effect on improving thermal stability; while increasing the ceramic content may affect ion conduction and increase battery weight. Therefore, it is of great significance to develop a new strategy that can improve the safety performance of the separator without reducing the energy density of the battery. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the present invention provides a diaphragm with an active coating for a battery and a preparation method thereof, which enhances the thermal stability and ion conductivity of the diaphragm, reduces the internal resistance of the battery, improves the charge and discharge efficiency and cycle life of the battery, and ensures the stable performance and safety of the battery.

[0007] The technical solution provided by the present invention is: a diaphragm with an active coating for a battery, comprising a diaphragm substrate and a composite coating coated on the diaphragm substrate, wherein the composite coating comprises an outer coating containing N-methyl-N-propylpyrrolidine bistrifluoromethanesulfonyl imide salt ([Pyr13][TFSI]) and an inner coating containing any one or more of polyacrylic acid (PAA), metal organic framework compounds (MOFs), modified boehmite, polyvinylidene fluoride (PVDF), and polymethyl methacrylate (PMMA).

[0008] Furthermore, the membrane matrix is ​​one or more of polyimide (PI), polyethylene terephthalate (PET), polypropylene / polyethylene (PP / PE), PP / PE / PP or PE / PP / PE composite film.

[0009] Furthermore, the coating slurry of the outer coating layer is obtained by mixing liquid N-methyl-N-propylpyrrolidine bistrifluoromethanesulfonyl imide salt, a binder, and a dispersant, and then adding the mixture into water and mixing evenly.

[0010] Furthermore, the weight ratio of N-methyl-N-propylpyrrolidine bistrifluoromethanesulfonyl imide salt: binder: dispersant: water in the coating slurry of the outer coating layer is 25-50: 3-15: 1-10: 40-70. The purity of [Pyr13][TFSI] is greater than 97%.

[0011] Furthermore, the binder is any one of polyvinylidene fluoride, styrene-butadiene rubber, and sodium carboxymethyl cellulose.

[0012] Furthermore, the dispersant is any one of polyethylene glycol, sodium hexametaphosphate, sodium polyacrylate, and polyvinyl pyrrolidone.

[0013] Furthermore, the thickness of the diaphragm substrate is 7-25 μm, the thickness of the outer coating is 2-25 μm, and the thickness of the inner coating is 2-10 μm.

[0014] Another technical solution provided by the present invention is a method for preparing a separator having an active coating for a battery, comprising the following steps:

[0015] (1) fully mixing and uniformly dispersing any one or more of polyacrylic acid, metal organic framework compound, modified boehmite, polyvinylidene fluoride, and polymethyl methacrylate with a binder, a dispersant, and water to form a coating slurry for an inner layer coating;

[0016] (2) adding N-methyl-N-propylpyrrolidine bis(trifluoromethanesulfonyl)imide salt, a binder and a dispersant into water according to a weight ratio, stirring and mixing them thoroughly and dispersing them uniformly to form a coating slurry for an outer coating layer;

[0017] (3) The coating slurry of the inner layer coating is coated on the surface of the diaphragm substrate and dried to obtain a composite diaphragm. Then, the coating slurry of the outer layer coating is coated on the surface of the composite diaphragm and dried to obtain a diaphragm with an active coating.

[0018] Furthermore, the coating speed of the inner layer coating is 50-80 m / min, and the drying temperature is 50-110°C.

[0019] Furthermore, the coating speed of the outer coating is 20-50 m / min, and the drying temperature is 80-110°C.

[0020] Beneficial effects of the present invention:

[0021] (1) The [Pyr13][TFSI] used in the present invention has high thermal stability and can withstand temperature changes during battery operation to a certain extent. Its molecular structure is relatively stable. Coating it on the diaphragm can enhance the thermal stability and ion conductivity of the diaphragm, while the potential harm to the environment is relatively small. At the same time, [Pyr13][TFSI] has good compatibility with lithium-ion battery electrolytes and is not prone to chemical reactions, ensuring the stability and safety of the battery performance. In addition, the diaphragm coated with [Pyr13][TFSI] can effectively improve the ion conductivity, reduce the internal resistance of the battery, and improve the charge and discharge efficiency and cycle life of the battery.

[0022] (2) The inner coating of the present invention can be coated on the diaphragm to form a close bond with the diaphragm base film, thereby enhancing the overall mechanical stability of the diaphragm and reducing the thermal conductivity of the diaphragm. In this way, during the manufacturing process of the battery, such as winding or lamination operations, the diaphragm can better withstand mechanical stress, reduce the separation of the base film and the coating, and when the battery is partially overheated, the heat will not be quickly transferred to the entire battery, thereby providing a certain buffer time for the thermal management of the battery, helping to control the temperature rise of the battery and reduce the risk of thermal runaway. DETAILED DESCRIPTION

[0023] A diaphragm with an active coating for a battery, the diaphragm with an active coating comprising a diaphragm substrate and two layers of diaphragm coatings coated on one side of the substrate, the inner layer of the coating being a composite diaphragm obtained by slurrying and coating the surface of the diaphragm substrate with one or more of polyacrylic acid (PAA), metal organic framework compounds (MOFs), modified boehmite and other ceramic materials or polyvinylidene fluoride (PVDF) or polymethyl methacrylate (PMMA), and drying; and the outer active coating layer being a composite diaphragm obtained by slurrying and coating the surface of the composite diaphragm with liquid [Pyr13][TFSI], a binder, a dispersant and the like in a certain proportion, and drying; the inner coating layer having a thickness in the range of 2-10 microns, and the outer active coating layer [Pyr13][TFSI] having a thickness in the range of 2-25 microns.

[0024] In order to further illustrate the technical means adopted by the present invention and the effects achieved, the following will be combined with specific embodiments to describe in detail a diaphragm with an active coating for a battery and a preparation method thereof according to the present invention, as well as the specific implementation methods, features and effects of the present invention. It should be noted in the following embodiments that the present invention is not limited to the following embodiments, and the embodiments disclosed in the present invention and the features therein can be combined with each other without conflict.

[0025] Example 1

[0026] A method for preparing a diaphragm having an active coating comprises the following steps:

[0027] 1) According to weight percentage, 25% polyacrylic acid, 60% water, 10% styrene-butadiene rubber and 5% polyethylene glycol are fully mixed and dispersed uniformly to form a polyacrylic acid coating slurry; the polyacrylic acid coating slurry is uniformly coated on one side of a 12-micron PP / PE / PP three-layer co-extruded film at a coating speed of 80 m / min, and then dried at a temperature of 70° C. to obtain a polyacrylic acid composite coating film with a thickness of 2 microns.

[0028] 2) adding [Pyr13][TFSI], a binder (polyvinylidene fluoride), a dispersant (sodium polyacrylate) and water into water at a weight ratio of 40:10:5:50, stirring and mixing thoroughly and dispersing uniformly to form a [Pyr13][TFSI] coating slurry; then uniformly coating the [Pyr13][TFSI] coating slurry on one side of the polyacrylic acid composite coating film obtained in step 1) at a coating speed of 30 m / min, and then drying at 105° C. to form a diaphragm with an active coating.

[0029] Example 2

[0030] A method for preparing a diaphragm having an active coating comprises the following steps:

[0031] 1) According to weight percentage, 35% modified boehmite, 50% water, 10% sodium carboxymethyl cellulose and 5% polyvinyl pyrrolidone are fully mixed and dispersed uniformly to form a modified boehmite coating slurry; the modified boehmite coating slurry is uniformly coated on one side of a 12-micron PP / PE / PP three-layer co-extruded base film at a coating speed of 60 m / min, and then dried at 80° C. to obtain a modified boehmite composite coating film with a thickness of 3 microns.

[0032] 2) adding [Pyr13][TFSI], a binder (styrene-butadiene rubber) and a dispersant (polyethylene glycol) into water at a weight ratio of 50:15:5:65, stirring and mixing thoroughly and dispersing the mixture evenly to form a [Pyr13][TFSI] coating slurry; then coating the [Pyr13][TFSI] coating slurry evenly on one side of the modified boehmite composite coating film obtained in step 1) at a coating speed of 35 m / min, and drying the coating slurry at 100° C. to form a diaphragm having an active coating.

[0033] Example 3

[0034] A method for preparing a diaphragm having an active coating comprises the following steps:

[0035] 1) According to weight percentage, 30% of metal organic framework compound (MOFs), 50% of water, 15% of styrene butadiene rubber and 5% of polyvinyl pyrrolidone are fully mixed and evenly dispersed to form a metal organic framework compound coating slurry; the metal organic framework compound coating slurry is evenly coated on one side of a 12-micron PP / PE base film at a coating speed of 50 m / min, and then dried at 80° C. to obtain a metal organic framework compound composite coating film with a thickness of 2.5 microns.

[0036] 2) adding [Pyr13][TFSI], a binder (sodium carboxymethyl cellulose) and a dispersant (sodium hexametaphosphate) into water at a weight ratio of 45:10:10:60, stirring and mixing thoroughly and dispersing uniformly to form a [Pyr13][TFSI] coating slurry; then uniformly coating the [Pyr13][TFSI] coating slurry on one side of the metal organic framework compound composite diaphragm obtained in step 1) at a coating speed of 30 m / min, and then drying at a temperature of 80° C. to form a diaphragm with an active coating.

[0037] Comparative Example 1

[0038] A comparative test was conducted using a 12 μm PP / PE / PP three-layer co-extruded film that was not subjected to coating treatment as Comparative Example 1.

[0039] Comparative Example 2

[0040] According to weight percentage, 35% polyacrylic acid, 50% water, 10% binder and 5% dispersant are fully mixed and dispersed evenly to form a polyacrylic acid coating slurry; the polyacrylic acid coating slurry is evenly coated on one side of a 12-micron PP / PE / PP film at a coating speed of 80 m / min, and then dried to obtain an aluminum oxide composite coating film with a thickness of 2 microns. The composite diaphragm coated with only a layer of polyacrylic acid is used as Comparative Example 2.

[0041] Comparative Example 3

[0042] [Pyr13][TFSI], a binder and a dispersant were added to a solvent in a weight ratio of 80:10:10, fully stirred and mixed and dispersed evenly to form a [Pyr13][TFSI] coating slurry; then the [Pyr13][TFSI] coating slurry was directly and evenly coated on one side of a 12-micron diaphragm substrate at a coating speed of 30 m / min, and then dried to form a diaphragm having only one layer of [Pyr13][TFSI] active coating. This coating film was used as Comparative Example 3.

[0043] Performance Testing

[0044] 1) Diaphragm thermal shrinkage test

[0045] The test method for the thermal shrinkage rate of the film material is as follows: cut the sample into 30cm×30cm test samples along the horizontal and vertical directions of the film sample, then clamp the cut sample in the middle of the newspaper, adjust the oven temperature to the set temperature, and fully preheat to ensure that the internal temperature is stable and reaches the set temperature, then put the prepared test sample together with the newspaper into the oven, and the sample should be placed in the middle of the upper layer of the oven. Set the test time to 1h according to the test requirements. After completion, take out the test sample film from the oven and wait for it to cool to room temperature, measure the distance between the horizontal / vertical diaphragm edges, and calculate the thermal shrinkage rate of the test sample film according to the thermal shrinkage rate calculation formula: thermal shrinkage rate n% = (initial length d1-length after heating d2) / initial length d1×100%.

[0046] 2) Mechanical properties test

[0047] The mechanical strength test method is as follows: cut the film to be tested into test samples of 15mm*200mm size, clamp the cut test samples on the clamps of the tensile testing machine, with the distance between the two clamps being 100mm, turn on the tensile testing machine, and perform a tensile strength test on the test samples at a speed of 50mm / min.

[0048] 3) Wetting performance test

[0049] The electrolyte is dropped onto the surface of the test sample using a contact angle tester, and the contact angle data of the test sample is recorded. The wetting properties of the diaphragm are evaluated by the contact angle of the electrolyte on the diaphragm.

[0050] 4) Conductivity test

[0051] The conductivity of the prepared separator samples was tested by assembling them into button cells.

[0052] The performance test results of Examples 1 to 3 and Comparative Examples 1 to 3 are shown in Table 1 below.

[0053]

[0054]

[0055] As can be seen from Table 1, the introduction of [Pyr13][TFSI] coating plays multiple roles: it not only enhances the thermal stability and wettability of the battery separator but also improves the ion transport performance of the battery.

[0056] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A separator with an active coating for a battery, characterized in that: The invention comprises a diaphragm substrate and a composite coating coated on the diaphragm substrate, wherein the composite coating comprises an outer coating containing N-methyl-N-propylpyrrolidine bistrifluoromethanesulfonyl imide salt and an inner coating containing any one or more of polyacrylic acid, metal organic framework compound, modified boehmite, polyvinylidene fluoride and polymethyl methacrylate.

2. A separator with an active coating for a battery according to claim 1, characterized in that: The membrane matrix is ​​one or more of polyimide, polyethylene terephthalate, polypropylene / polyethylene, polypropylene / polyethylene / polypropylene or polyethylene / polypropylene polyethylene composite film.

3. A separator with an active coating for a battery according to claim 1, characterized in that: The coating slurry of the outer coating layer is obtained by mixing liquid N-methyl-N-propylpyrrolidine bistrifluoromethanesulfonyl imide salt, a binder and a dispersant, and then adding the mixture into water and mixing evenly.

4. A separator with an active coating for a battery according to claim 3, characterized in that: The weight ratio of N-methyl-N-propylpyrrolidine bistrifluoromethanesulfonyl imide salt: binder: dispersant: water in the coating slurry of the outer coating layer is 25-50: 3-15: 1-10: 40-70.

5. The separator with active coating for battery according to claim 3, characterized in that: The binder is any one of polyvinylidene fluoride, styrene-butadiene rubber and sodium carboxymethyl cellulose.

6. A separator with an active coating for a battery according to claim 3, characterized in that: The dispersant is any one of polyethylene glycol, sodium hexametaphosphate, sodium polyacrylate and polyvinyl pyrrolidone.

7. A separator with an active coating for a battery according to claim 1, characterized in that: The thickness of the diaphragm substrate is 7-25 μm, the thickness of the outer coating is 2-25 μm, and the thickness of the inner coating is 2-10 μm.

8. A method for preparing a separator with an active coating for a battery according to any one of claims 1 to 7, characterized in that: The steps include: (1) fully mixing and uniformly dispersing any one or more of polyacrylic acid, metal organic framework compound, modified boehmite, polyvinylidene fluoride, and polymethyl methacrylate with a binder, a dispersant, and water to form a coating slurry for an inner layer coating; (2) adding N-methyl-N-propylpyrrolidine bis(trifluoromethanesulfonyl)imide salt, a binder and a dispersant into water according to a weight ratio, stirring and mixing them thoroughly and dispersing them uniformly to form a coating slurry for an outer coating layer; (3) The coating slurry of the inner layer coating is coated on the surface of the diaphragm substrate and dried to obtain a composite diaphragm. Then, the coating slurry of the outer layer coating is coated on the surface of the composite diaphragm and dried to obtain a diaphragm with an active coating.

9. The method for preparing a separator with an active coating for a battery according to claim 8, characterized in that: The coating speed of the inner layer coating is 50-80 m / min, and the drying temperature is 50-110°C.

10. The method for preparing a separator with an active coating for a battery according to claim 8, characterized in that: The coating speed of the outer coating is 20-50 m / min, and the drying temperature is 80-110°C.

Citation Information

Cited By

  • Composite multifunctional battery diaphragm as well as preparation method and application thereof

    CN120933599A